Trends in Trade and Logistics : An East Asian Perspective - Carruthers, Robin; Bajpai, Jitendra N. (World Bank, Washington, DC, 2014)
There are five sections in this report. The first section analysis growth, poverty reduction, trade and logistics. The study indicates that a stimulus in economic growth tends to reduce poverty. Section two analysis global trends in transport and logistics that determine the competitive advantage and growth performance of trading in global economy. Transport and logistics have benefited from technological and institutional changes, and has developed the maritime transport, warehousing facilities, and communication. The net result has been to facilitate globalization. Section three analysis trade led growth in East Asia. The sustained growth performance is usually attributed to the region's global integration. Section four: Logistics in East Asia - the single most important impact of globalization in East Asian countries has been the integration of local production and supply. Section five - a strategy to stimulate trade-led poverty reduction. This analysis has demonstrated the significance of the role of trade in accelerating economic growth and reducing poverty. In addition, the trade pattern of the region is focused in terms of final market destination.